Kemampuan motorik kasar anak di sekolah sepak bola (ssb) - Sadikin, Muhammad; Ahmad, Ahmad; Ulpi, Wahyuni (Universitas Hamzanwadi, 2023)
The problem in this study is the lack of gross motor skills of children in their daily lives and activities. The goal is that the basic abilities of children are seen from their physical motor abilities, so the trainer will help improve children's physical or motor skills in terms of introducing and training children's gross and fine motor movements, increasing the ability to manage, control body movements, and coordination, as well as improving body skills and a healthy way of life so that they can support strong, healthy and skilled physical growth. The research method used was descriptive qualitative. The population is 30 ssb players aged 6-18 years. Sampling using purposive sampling technique, samples were taken aged 6-8 years with 5 people. Data analysis techniques are collecting data, data reduction, data presentation, and conclusion drawing. This research can be concluded that gross motor skills have a significant impact on soccer sports, because basically gross motor skills are the ability to move the body using large muscles that are needed so that children can do passing, dribbling, shooting well.